Comparison of growth and production of Holstein heifers raised on 100% or 115% of the NRC requirements - E.J. Bortone; M. G. Daccarett; J.L. Morrill; A.M. Feyerherm (Kansas Agricultural Experiment Station Research Reports, 1990)
One hundred and ten Holstein heifers from the KSU Dairy Research Unit were used in this experiment. They were fed either 100% (control) or 115% (enhanced) of NRC requirements for energy, protein, major minerals, and vitamins from 6 mo of age to shortly before calving. Heifers in the enhanced group calved at an earlier age, had larger heart girths, and were heavier than controls. At this time, 46 of the heifers have completed at least 50 days in lactation. Based on their projected 305-2X-ME records, the heifers in the enhanced group have produced slightly, but not significantly, more milk and milk fat.; Dairy Day, 1990, Kansas State University, Manhattan, KS, 1990; The 1990 Annual KSU Dairy Day is known as Dairy Day, 1990
Keywords: Dairy Day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-148-S; Report of progress (Kansas Agricultural Experiment Station); 608; Dairy; NRC requirements; Holstein heifers; Growth and production